P.103 A spatial analysis of forces applied during virtual reality brain tumor resection: the force pyramid. (17th June 2016) - Del Maestro, RF; Azarnoush, H; Siar, S; Alzhrani, G; Winkler-Schwartz, A; Alotaibi, F; Bajunaid, K; Sawaya, R; Bugdadi, A; Marwa, I
Abstract : Background: Virtual reality simulators allow development of novel methods to analyze neurosurgical performance. Force pyramids provide visual and spatial analysis of 3 dimensional force application by any instrument used during simulated tumor resection. This study was designed to answer three questions: 1) Do study groups have distinct force pyramids? 2) Do handedness and ergonomics influence force pyramid structure? 3) Are force pyramids dependent on visual and haptic characteristics of simulated tumors?Methods: NeuroVR (formerly NeuroTouch), a virtual reality simulator, continually assessed simulated ultrasonic aspirator force application of neurosurgeon, resident and medical student groups during resection of 18 simulated brain tumors with different visual and haptic characteristics.Results: Sixteen neurosurgeons, 15 residents and 84 medical students participated. Neurosurgeon, resident and medical students groups displayed easily distinguishable 3 dimensional 'force pyramid fingerprints'. Neurosurgeons had the lowest force pyramids, indicating application of the lowest forces, followed by resident and medical student groups. Handedness, ergonomics, visual and haptic tumor characteristics resulted in distinct well-defined 3 dimensional force pyramid patterns.Conclusions: 'Force pyramid fingerprints' provide 3 dimensional spatial assessment displays of instrument force application during simulated tumor resections. Neurosurgeon force utilization and ergonomics data form a basis for understanding and modulating resident force application and improving patient safety during tumor resection.